Genomic characterization of co-existing neoplasia and carcinoma lesions reveals distinct evolutionary paths of gallbladder cancer - Jianzhen Lin (Nature Portfolio, 2021)
The progression from biliary tract intraepithelial neoplasia (BilIN) to gallbladder carcinoma (GBC) remains unclear. Here the authors use genomics to analyze coexisting GBC lesions, low-grade and high-grade BilINs, revealing two distinct evolutionary paths for GBC development.